PERAN GURU PAI DALAM MENGINTEGRASIKAN NILAI-NILAI ISLAMI TENTANG KESEHATAN DAN KESEJAHTERAAN DALAM PROGRAM MAKAN BERGIZI GRATIS - Fuji Arifzapni; Martin Kustanti; Gusmirawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of Islamic Education (PAI) teachers in integrating Islamic values related to health and well-being into the free nutritious meal program in schools. Such integration is essential for fostering students’ spiritual and social awareness regarding the importance of maintaining health as a form of responsibility entrusted by Allah SWT. This research employed a descriptive qualitative method, with data collected through observations, interviews, and documentation involving PAI teachers, students, and program administrators. The findings indicate that PAI teachers play a strategic role in imparting Islamic values such as gratitude, cleanliness, responsibility, and social care through both instructional activities and daily habituation. The integration of these values not only enhances students’ spiritual understanding but also shapes healthy living behaviors and strengthens social solidarity within the school environment.